Development and psychometric validation of the hospitalized patients’ expectations for treatment scale-patient version - Xiao, Chunfeng; Wu, Aoxue; Wang, Yufei; Li, Tao; Duan, Yanping; Jiang, Yinan; Shi, Lili; Hong, Xia; Geng, Wenqi; Li, Jiarui; Du, Jianhua; Hu, Jiaojiao; et al. (Frontiers in Psychiatry, 2023)
A general expectation measurement of inpatients across wards is needed in the patient safety management systems of general hospitals. This study developed and psychometrically validated a new scale fulfilling the requirements above: the Hospitalized Patients' Expectations for Treatment Scale-Patient version (HOPE-P). A total of 35 experts and ten inpatients were interviewed during the formulation of the HOPE-P scale, which was initially designed with three dimensions: doctor–patient communication expectations, treatment outcome expectations, and disease management expectancy. We recruited 210 inpatients from a general hospital in China and explored the reliability, validity, and psychometric characteristics of the questionnaire. Item analysis, construct validity, internal consistency and 7-day test–retest reliability analysis were applied. Exploratory and confirmatory analyses supported a 2-dimension (doctor–patient communication expectation and treatment outcome expectation) structure with satisfactory model fit parameters (root mean square residual (RMR) = 0.035, a root-mean-square-error of approximation (RMSEA) = 0.072, comparative fit index (CFI) = 0.984, Tucker-Lewis index (TLI) = 0.970). Item analysis revealed an appropriate item design (r = 0.573–0.820). Internal consistency of developed instrument was good, for the overall scale (Cronbach’s α = 0.893, 95% CI = [0.869, 0.913]), Subscale A (Cronbach’s α = 0.761, 95% CI = [0.699, 0.812]), and Subscale B (Cronbach’s α = 0.919, 95% CI = [0.900, 0.935]). McDonald's ω coefficients of the HOPE-P full scale, subscale A and B were 0.890 (95% CI = [0.867, 0.913]), 0.761 (95% CI = [0.705, 0.817]), and 0.921 (95% CI = [0.904, 0.938]), respectively. The 7-day test–retest reliability was 0.670 (p = .001). Our results indicated that the HOPE-P is a reliable and valid assessment tool to measure the expectations of general hospital inpatients, with a strong capacity to recognize patients’ expectations regarding doctor–patient communication and treatment outcomes.